2021
DOI: 10.4266/acc.2021.00017
|View full text |Cite
|
Sign up to set email alerts
|

Airway pressure release ventilation in mechanically ventilated patients with COVID-19: a multicenter observational study

Abstract: Background: There is high prevalence of severe hypoxia, use of invasive mechanical ventilation, and high mortality in patients with severe coronavirus disease 2019 (COVID-19) pneumonitis. Evidence prior to the COVID-19 pandemic suggested that, compared with conventional ventilation strategies, airway pressure release ventilation (APRV) can improve oxygenation and reduce mortality in patients with acute respiratory distress syndrome. We aimed to assess the association between APRV use and clinical outcomes amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…The pooled reported C RS in patients from studies of unselected COVID-19-related ARDS was 35·8 mL/cm H 2 O (95% CI 33·9–37·8; I 2 =96·9%, τ 2 =32·6; high certainty; figure 2 ). 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 In these studies, C RS dispersion was not significantly different from a normal distribution (Shapiro-Wilk test p=0·92; figure 3 ). The pooled reported C RS in all patients from studies of selected and unselected COVID-19-related ARDS was 34·7 mL/cm H 2 O (32·8–36·6; 97·2%, 43·6; high certainty; appendix p 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled reported C RS in patients from studies of unselected COVID-19-related ARDS was 35·8 mL/cm H 2 O (95% CI 33·9–37·8; I 2 =96·9%, τ 2 =32·6; high certainty; figure 2 ). 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 In these studies, C RS dispersion was not significantly different from a normal distribution (Shapiro-Wilk test p=0·92; figure 3 ). The pooled reported C RS in all patients from studies of selected and unselected COVID-19-related ARDS was 34·7 mL/cm H 2 O (32·8–36·6; 97·2%, 43·6; high certainty; appendix p 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results do not advocate against the use of high-flow oxygen or for early intubation, but open doors for further research and emphasize caution when dealing with these patients with ARDS. In both study groups, we did not employ airway release pressure ventilation, and recent research has advocated against its use in COVID-19 patients with ARDS [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… [37] , [38] , [39] Recently, Mahmoud et al [40] found that APRV may improve oxygenation, alveolar ventilation, and CO 2 clearance in patients with COVID-19 and refractory hypoxemia. Moreover, Zorbas et al [41] urged caution with the use of APRV in patients with COVID-19.…”
Section: Application Of Aprv In Ardsmentioning
confidence: 99%